Application of the Problem Based Learning (PBL) learning model to improve learning outcomes and reading skills in Indonesian class 1 subject at SDN 02 Girimoyo - Nadela Susdiawanti Nadela Susdiawanti; Gigit Mujianto; Kholiq Yudiantoro (Jurnal Bidang Pendidikan Dasar, 2023)
The purpose of this study was to improve learning outcomes and reading skills through the PBL learning model for grade 1 students at SDN 02 Girimoyo. The research method used is PTK (Classroom Action Research) based on Lesson Study using 2 research cycles. Each cycle consists of plan, do, see. The research subjects were all 30 students in class 1-A at SDN 02 Girimoyo (13 girls and 17 boys). The results of the study explain that the average percentage of cycle 1 is 73.96%, the classical learning completeness is 43.33% and there is an increase in learning outcomes and reading skills in cycle II with an average percentage of 85% and the classical learning mastery is 86.67%. From these results, it can be concluded that the application of the PBL learning model.